Price risk and small farmer maize storage in Sub‐Saharan Africa: New insights into a long‐standing puzzle. Issue 3 (6th September 2022) - Cardell, Lila; Michelson, Hope
Abstract: Maize prices fluctuate across seasons in rural markets in many low income countries, and agricultural households struggle to sell their grain at an optimal time. We provide new insight into a persistent puzzle: small farmers in low‐income countries tend to sell their maize at harvest, when prices are low, rather than storing and waiting until prices increase later in the year. Our descriptive analysis uses 20 years of data from 1038 retail markets in 30 African countries to demonstrate that the lean season price (the "high price" season) fails to rise above the harvest season price (the "low price" season) 16.3% of the time on average in countries with a single maize season and between 15.9% and 24.9% on average in countries with two maize seasons. On the basis of that stylized fact, we propose that aversion to these negative returns may contribute to farmers' decisions to opt out of storage at harvest. Using a smaller dataset of 425 retail markets in 10 countries with a single maize season, we show that even moderately risk averse farmers would opt out of storage in 15.3% of market years. Farmers cannot always predict returns to storage and output price risk may dissuade farmers from storing maize for the purpose of future sales, despite credit access. Our results indicate that other mechanisms, such as forward contracts or multiyear credit, may be necessary to mitigate downside price risk.